2013
DOI: 10.1177/0886260512468229
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors of Same-Sex Intimate Partner Violence in Hong Kong

Abstract: Numerous studies have assessed risk and protective factors for intimate partner violence (IPV) among heterosexual couples around the globe. Nevertheless, few have addressed the same issue among same-sex couples, especially in cultures where same-sex intimate relationships have gained little acceptance. This exploratory study evaluated the substantial risk and protective factors for same-sex IPV based on gender-neutral theories. Three hundred and six Hong Kong residents who have been in a same-sex romantic rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 42 publications
4
44
0
5
Order By: Relevance
“…For example, Finneran and Stephenson (2014) found that internalized homophobia was associated with the perpetration of sexual IPV in men who have sex with men. Nevertheless, this association between internalized homophobia and IPV is not consistent across studies (Bartholomew, Regan, Oram, & White, 2008; Carvalho, Lewis, Derlega, Winstead, & Viggiano, 2011; Chong et al, 2013; McKenry, Serovich, Mason, & Mosack, 2006; Pepper & Sand, 2015).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…For example, Finneran and Stephenson (2014) found that internalized homophobia was associated with the perpetration of sexual IPV in men who have sex with men. Nevertheless, this association between internalized homophobia and IPV is not consistent across studies (Bartholomew, Regan, Oram, & White, 2008; Carvalho, Lewis, Derlega, Winstead, & Viggiano, 2011; Chong et al, 2013; McKenry, Serovich, Mason, & Mosack, 2006; Pepper & Sand, 2015).…”
mentioning
confidence: 75%
“…These studies have documented that rates of IPV in lesbian, gay, and bisexual (LGB) individuals are equal to or even greater than rates observed in heterosexual individuals (Ard & Makadon, 2011; Badenes-Ribera, Bonilla-Campos, Frias-Navarro, Pons-Salvador, & Monterde-i-Bort, 2016; Edwards, Sylaska, & Neal, 2015; Finneran & Stephenson, 2013; Goldberg & Meyer, 2013; Hellemans, Loeys, Buysse, Dewaele, & De Smet, 2015; Nowinski & Bowen, 2012; Walters, Chen, & Breiding, 2013). Furthermore, risk factors for IPV in LGB individuals have shown some similarities with IPV in heterosexual individuals, but they have also included unique factors, such as those related to their sexual minority identity, which may help to explain higher IPV rates in LGB individuals (Badenes-Ribera et al, 2016; Chong, Mak, Mabel, & Kwong, 2013; Edward et al, 2015; Lewis, Milletich, Kelley, & Woody, 2012; Mason et al, 2014).…”
mentioning
confidence: 99%
“…The associated adverse health consequences for female victims include depression, anxiety, post-traumatic stress disorder, eating disorders [4],[5], and sexual and reproductive health problems [6],[7]. However, intimate partner violence (IPV) is not exclusive to opposite-sex relationships, and there is a growing body of research highlighting the prevalence of IPV in same-sex relationships [8][14]. Recent reviews suggest that the prevalence in same-sex couples, in particular male–male couples, is as high as or higher than it is for women in opposite-sex relationships [15][18].…”
Section: Introductionmentioning
confidence: 99%
“…Por forma a ultrapassar os problemas existentes na investigação nesta área, estudos futuros devem utilizar um conceito uniformizado no que diz respeito à definição da problemática e à definição das tipologias de violência entre parceiros íntimos, metodologias (Barros et al, 2019;Chong, Mak, & Kwong, 2013) e instrumentos específicos do estudo do fenômeno na vertente homossexual, fazer distinção na análise dos dados (i.e., vítimas -perpetradores; masculino -feminino) (Badenes-Ribera et al, 2015;Finneran & Stephenson, 2012), utilizando amostras representativas (Roberts, 2005). Seria, também, interessante investir-se no estudo da problemática da saúde mental no contexto da violência em relacionamentos homossexuais, com a finalidade de se explorar se a mesma influencia, de algum modo, a vitimização e/ou a perpetração de violência, assim como investir-se na realização de estudos longitudinais, o que em Portugal se afigura escasso.…”
Section: Recomendações Para Estudos Futurosunclassified